TINJAUAN PUSTAKA AKSES YANG TIDAK SETARA TERHADAP PEMERIKSAAN KANKER SERVIKS: PERSPEKTIF GENDER DAN KESEHATAN PUBLIK DI ERA DIGITAL - Indira, Syalisa Mei; Ernawati, Ernawati (Rena Cipta Mandiri, 2025)
Cervical cancer is a global health problem, with 85-90% of cases and deaths occurring in low- and middle-income countries due to limited screening availability. This study used a qualitative review of 20 scientific papers (2021-2025) to investigate disparities in screening availability and digital advances such as AI, telehealth. Findings suggest that digital tools improve diagnostic accuracy and user consent, such as AI-driven sensitivity and self-sampling willens access for rural women and individuals with disabilities. However, barriers such as inadequate facilities, hidden costs, social bias, scarcity of medical staff, and systemic discrimination continue to limit engagement. Use of technology without support from digital literacy, culturally aware conversations, and gender-friendly rules may further exacerbate the divide. In short, screening programs must be open, inclusive, and combine digital advances with national referral networks and equity – to ensure cervical cancer screening is available and equitable for all.